Nature-inspired algorithms for big data frameworks - Banati, Hema 1970-; Mehta, Shikha 1977-; Kaur, Parmeet 1976- (IGI Global, 2018)
"This book focuses on application of nature-inspired algorithms for handling issues and challenges posed by big data in diverse environments. It highlights the usability and performance measures of these techniques in dealing with data related problems of emerging areas. It also explore the role of machine learning techniques for the optimization and learning involving data intensive applications"--